The changes of horizontal distance condyle to nasal septum after the Twin-block treatment on class II division 1 with retrognathic mandible - Xin, Lee Jie; Mardiati, Endah; Harsanti, Andriani (Universitas Padjadjaran, 2016)
Introduction: Twin-block appliance is simple removable bite block mostly used in the management of Class II malocclusion. It can modify the occlusal inclined plane to guide the mandible protrusion. Hence, when the patients are wearing the Twin-block appliances, this altered biomechanical environment and will stimulate the growth of the secondary cartilage of condyle and will caused the condyle to change in size, volume or position the in long term. The aim of this study was to investigate the changes of horizontal distance from condyle to nasal septum after the Twin-block treatment on Class II division 1 with retrognathic mandible. Methods: There were total 5 samples of panoramic radiograph before Twin-block treatment and 5 samples of panoramic radiograph after Twin-block treatment. The panoramic radiographs were traced to identify the changes of horizontal distance from condyle to nasal septum after the Twin-block treatment. The distance from the middle of nasal septum to the most superior surface of condyle head for right region and left region were measured, then the differences were statistically analyzed. Results: The horizontal distance from the middle of nasal septum to the most superior surface of condyle head after the Twin-block treatment increased. The difference of condyle position before and after the treatment of Twin-block.was slight (p-value > 0.05). Conclusion: There is no significant difference in horizontal distance from the most superior surface of condyle head to the middle of nasal septum before and after treatment of Twin-block.